El doble meandro abandonado del Guadalquivir en Cantillana (Sevilla): cambios de trazado y evolución geomorfológica - García Martínez, Belén; Baena Escudero, Rafael (Geographicalia, 2015)
This paper shows the evolution of the double meander of the Guadalquivir River in Cantillana (Seville) during the last stage of its fluvial history. Regarded as a river of great quaternary evolution, it presents a winding course since the end of the Holocene. Its process of inactivity began in the mid-20th century due to the overflowing of its main tributary, the Viar River, which made several paleochannels on the flood plain functional again. Its transition stage should be considered short-termed since the river recovers its functionality at times of the floods.
Keywords: Cut-neck; Oxbow Meanders; fluvial Geomorphology; Guadalquivir River; Cantillana; Seville.